Financial Reporting Transparency and the Cost of Equity: Evidence From Newly Listed Firms - Cheng, Yang; Alam, Pervaiz; Hou, Liya (Journal of Applied Business and Economics, 2024)
This paper explores the economic effects of financial reporting transparency of newly listed firms and outcomes associated with enhanced disclosure and financial reporting activities. We find a negative correlation between financial reporting transparency and information asymmetry in newly listed firms during their first five years of public trading. Further, we find a significant positive link between perceived business risk and implied cost of equity for these new public companies. Furthermore, we find a positive association between financial reporting transparency and the cost of equity. Our study helps to extend the research on the consequences of increased disclosures of newly listed firms.